2016
DOI: 10.1371/journal.pone.0165480
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Children’s Surgical Care in Low- and Middle-Income Countries: A Systematic Review and Analysis

Abstract: BackgroundUnderstanding the economic value of health interventions is essential for policy makers to make informed resource allocation decisions. The objective of this systematic review was to summarize available information on the economic impact of children’s surgical care in low- and middle-income countries (LMICs).MethodsWe searched MEDLINE (Pubmed), Embase, and Web of Science for relevant articles published between Jan. 1996 and Jan. 2015. We summarized reported cost information for individual interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 103 publications
(41 reference statements)
1
82
0
1
Order By: Relevance
“… 15 , 16 , 17 Many areas of surgical care for children are cost-effective and in appropriate settings can provide financial protection against medical impoverishment to families in need. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 , 17 Many areas of surgical care for children are cost-effective and in appropriate settings can provide financial protection against medical impoverishment to families in need. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…There are also concerns about cost-effectiveness and long-term impact. 7,33 Current results, however, suggest a positive impact of such collaborations. A recent meta-analysis demonstrated that many surgical interventions, including surgical treatment of hydrocephalus ($108.74 per disability-adjusted life year), are, in fact, cost-effective in resource-poor countries.…”
Section: Difficulties and Limitations Of The Different Modelsmentioning
confidence: 89%
“…Our utilitarian analysis supports the conclusions of others, who have stated, based on cost-effectiveness, that addressing the global deficit of surgical care is a "moral imperative", 8 and have named congenital heart surgery, in particular, as one of the "essential children's surgical procedures". 21 The most recent recommendation of the Disease Control Priorities project, 24 although less specific, suggests that "all countries can begin to consider building capacity for the treatment of CHD".…”
Section: Cost-effectiveness and Humanitarian Medicinementioning
confidence: 99%